Culture and Family’s Class in Jamaica Kincaid’s Girl - Hendriani, Ria; Herman (HAMJAH DIHA FOUNDATION bekerjasama dengan PENA INSTITUTE, 2022)
Jamaica Kincaid’s short fiction “Girl” revolves around the stream of consciousness interaction between two women, a mother and a daughter. It was an unconventional text that portrays a mother’s list of rules that her daughter must obey in order to be accepted in society. The aim of this research was to find culture and family’s clash in Jamaica Kincaid’s “Girl”. The method used in this research was the qualitative method with a narrative approach. In this short fiction, culture has an impact on the clash of mother and the child; moreover the mother-child relationship at stake. Mother’s concept that is influenced by culture breaks her relationship with her child because she always tries to make her child appreciated by the society by teaching her culture implicitly. Whereas, child’s concept is far away from culture because she attracts to play and get happiness; it is contrasted with her mother. Every mother has their own experiences in mothering their children which will distinguish it with each other based on their children’s needs. It is important for mother to recognize the special characteristics of their children and accept them as they are. Mother should push aside their personal expectations, focus on what their children wish to accomplish and realize that their children are not their continuation but they have a life of their own. It’s best then for them to let their kids set their own targets according to what the children want and need. It is not healthy for mother to live vicariously through her daughter or try to make her daughter be like them. They should not to dictate their daughters’ goals, but it is better to guide them and support them in learning to set goals themselves.